THE INTENSITY OF SUEDE KERMEK (LIMONIUM TOMENTELLUM (BOISS.) KUNTZE) PHYSIOLOGICAL PROCESSES - Орлова, Л.Д.; Котелевська, А.О. (World of Medicine and Biology, 2015)
A study was conducted of the indicators of intensity of physiological processes in a typical representative of the halophytic flora Limonium tomentellum (Boiss.) Kuntze vicinities of Kremenchug district, Poltava region. It was determined the intensity of respiration, transpiration and photosynthesis. It is shown that the intensity of photosynthesis, transpiration and respiration affected by temperature, humidity and lighting. In addition, all the indicators are linked. Between the intensity of photosynthesis and intensity of breathing there is an inverse relationship: the maximal intensity of the breath are traced at high temperatures and dry air, and the rate of photosynthesis at optimal temperature and moisture. The intensity of physiological parameters Limonium tomentellum shows its variability and changeability.